Greek and Roman slavery - Wiedemann, Thomas E. J. (Routledge, 1988)
Greek and Roman Slavery brings together fresh English translations of 243 texts and inscriptions on slavery from fifth and fourth century Greece and Rome. The material is arranged thematically, offering the reader a comprehensive review of the idea and practice of slavery in ancient civilization. In addition, a thorough bibliography for each chapter, as well as an extensive index, make this a valuable source for scholars and students.